العدالة التنظيمية و دورها في تعزيز سلوكيات المواطنة التنظيمية )دراسة استطالعية الراء عينة من العاملين في مستشفى EMC في مدينة اربيل( - م.م. زانا مجيد صادق – جامعة كوية - محاضر في الجامعة اللبنانية الفرنسية - اربيل (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The study aims to measure the role of organizational justice in promoting the behavior of organizational citizenship among workers in EMC’s Hospital in the city of Erbil. A questionnaire has been designed and developed in order to collect data from a study sample in order to achieve the objectives of this study and testing the main hypothesis as well as sub- hypothesis (relationship and impact). The study found that the perceptions of respondents about the level of organizational justice (distributive justice, procedural justice, justice, interactive, and evaluative justice) is high at EMC hospital. The perceptions of respondents about the level of the concept of the behavior of organizational citizenship level (altruism, courteous, conscientious, and civilized behavior) in EMC hospital is high, while the sporting spirit was at medium level. Furthermore the study found that there is a positive correlation and high impact oforganizational justice on organizational citizenship behaviors. In light of these results it has been formulated a number of recommendations to promote the structure of organizational citizenship behaviors among workers in the surveyed organization.